Lokativna alternacija u engleskom i hrvatskom - Zovko Dinković, Irena (Array, 2003)
This paper discusses the locative alternation, a type of alternation that involves transitive verbs taking more than one VP-internal argument. This alternation allows location arguments to alternate with theme arguments and thus become realized as the direct object (i.e. the primarily affected entity). The paper attempts to give a theory-neutral overview of locative alternation in English in comparison with Croatian. Our analysis shows that locative alternation in Croatian is expressed through both derivational morphology and a kind of alternating parallel to English. We may conclude that even though verb alternations carry different semantic implications and restrictions in different languages, they still remain a valuable tool for determining the relevant semantic properties through grammatical means.